VD_FINDINFO HC / 2013 / 452 vom 12. August 2013 - VD Tribunal cantonal (2013)
EXPULSION DE LOCATAIRE, ABUS DE DROIT, BAIL À LOYER, LOCAL PROFESSIONNEL | 2 al. 2 CC, 2 CC, 1 al. 2 CO, 257d CO, 243 al. 2 let. c CPC (CH)